Effect of Behaviour Modification Strategies on Secondary School Students’ Classroom Misbehaviour - Aslam, Shumaila; Farooq, Prof.Dr. Muhammad Shahid (PJE, 2024)
Misbehaviour in the classroom disrupts students' attention and negatively affects the teaching-learning process. Every learner has certain needs, and when these needs are not met at a critical moment, students start acting up in class. The best way to deal with a disruptive student is to take preventative measures. A causal comparative research design was used to examine the effect of teaching strategies on students’ classroom misbehaviour and find out the difference between male and female students’ perception about the classroom misbehaviors at secondary school level. The sample of the study was 408 students, selected by randomly from 34 public secondary schools in district Lahore. A self-developed instrument was used for data collection. The findings of the study show that students engage in misbehaviour i.e. skipping class, sleeping in the classroom, blaming the teaching method and cheating in tests/examinations.Teachers used strategies to deal with student misbehavior, including hand slapping, hitting with sticks, bending and slapping, and calling students names. There is a significant difference between male and female students’ perception about misbehaviors. Punitive strategies have a significant effect on students’ misbehaviours. Instructional and advisory committees should be established in schools to advise teachers on the psychological needs of students. Teachers should be introduced to innovative teaching strategies to deal with student misbehaviour. Different new courses may be included in the curriculum of pre- service teacher training programs.